A Cycloartane Triterpenoid and Steroid from The Leaves of Aglaia shawiana Merr. (Meliaceae) - Ricson Pemimpin Hutagaol; Miskah Yumna; Heriansyah Rangkuti; Tjandrawati Mozef; Sofa Fajriah; Gian Primahana; Muhammad Eka Prasetya (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Natural products and their structural analogs are the main sources of pharmacotherapy. Various Aglaia species have been investigated since the 1960s for their phytochemical constituents and biological properties. This research focuses on isolating the terpenoid group from Aglaia shawiana, to provide a basis for further research to identify lead compounds for drug development. The hexane extract of Aglaia shawiana leaves was isolated using vacuum liquid chromatography and gravity column chromatography, employing solvents with varying polarities. The isolation process yielded two compounds: compound 1 and compound 2. A total of 15 mg of a pure isolate was obtained for compound 1, and 4.5 mg for compound 2. Their structures were characterized using 1D NMR (¹H, 13C, DEPT 135) and 2D NMR (HMQC, HMBC, 1H-1H COSY) and by comparing them with previously reported spectral data. It was concluded that compound 1 has the molecular formula C30H50O3, is a triterpenoid type cycloartane, and is named cycloartan-3β,29-diol-24-one, while compound 2 has the molecular formula C30H52O, is a steroid compound, and is named 23a-homostigmast-5en-3β-ol. These compounds were discovered for the first time in this species.